Do STAD Learning Method Can Improve Students' Learning Outcomes on Social Science? - Fatkul Anam; Nur Asitah; Agung Purnomo; Muawwinatul Laili; Dhana Qurrota A’yun (Indonesian Journal of Islamic Education Studies (IJIES), 2021)
Some students in elementary schools face some problems related to the students’ learning focus and interest in a social science subject. The Student Teams Achievement Divisions (STAD) of the cooperative learning model on educational management divides students into small teams to discuss and help each other. This study purposes to improve elementary school students’ learning outcomes focus on social science subjects using the STAD learning method. The implementation of the STAD learning method in this research is based on the Classroom Action Research model which was developed by Kurt Lewin. This model involves four stages, namely; planning, acting, observing, and reflecting. The result of this study proves that the applying of the STAD learning method on social science subjects in fourth-grade elementary students can improve the students’ learning outcomes, role, enthusiasm, and cooperation between others in the learning process. It can be seen from the increase of students’ learning outcomes completeness reach up to 80,9%.